Leptin: A new aspect of a multifunctional protein - El-Yassin D. Hedef (College of Pharmacy / Mustansiriyah University, 2004)
The Maintenance of an appropriate body weight is very important for the survival of higher organisms. In order to have a constant weight, there must be an energy balance. Despite short-term mismatches in energy balance, energy intake can generally be matched to energy expenditure with great precision due to the existence of several types of signaling biomolecules such as leptin. Leptin is an adiposity-derived hormone that decreases food intake and body weight via its receptor in the hypothalamus. In rodents, it also modulate glucose metabolism by increasing insulin sensitivity. Leptin interacts with pathways in central nervous system and through direct peripheral mechanisms. Leptin appears to have a range of roles as a growth factor in a range of cell types. Surely, more interactions are yet to be discovered. Although the complexity of leptin axis indicates that it is difficult to derive effective treatments for obesity, leptin was the first of a group of adiposite-secreted hormones to be used clinically to treat hypoleptinemic status. This review sheds a small ray of light on the wide landscape of function, roles, actions and interactions of leptin to improve knowledge and point the way to the underlying physiology which predisposes some individuals to apparently unregulated weight gain